Prevalence and population structure of Staphylococcus aureus nasal carriage in healthcare workers in a general population. The Tromsø Staph and Skin Study - Olsen, Karina; Sangvik, Maria; Simonsen, Gunnar Skov; Sollid, Johanna U Ericson; Sundsfjord, Arnfinn; Thune, Inger; Furberg, Anne-Sofie (Epidemiology and Infection, 2013)
This article is part of Karina Olsen's doctoral thesis, available in Munin at http://hdl.handle.net/10037/5596 Healthcare workers (HCWs) may be a reservoir for Staphylococcus aureus transmission to patients. We examined whether HCW status is associated with S. aureus nasal carriage and population structure (spa types) in 1302 women (334 HCWs) and 977 men (71 HCWs) aged 30–69 years participating in the population-based Tromsø Study in 2007–2008. Multivariable logistic regression models were used. While no methicillin-resistant S. aureus (MRSA) was isolated, overall, 26·2% of HCWs and 26·0% of non-HCWs were S. aureus nasal carriers. For women overall and women residing with children, the odds ratios for nasal carriage were 1·54 [95% confidence interval (CI) 1·09–2·19] and 1·86 (95% CI 1·14–3·04), respectively, in HCWs compared to non-HCWs. Moreover, HCWs vs. non-HCWs had a 2·17 and 3·16 times higher risk of spa types t012 and t015, respectively. This supports the view that HCWs have an increased risk of S. aureus nasal carriage depending on gender, family status and spa type.